Sappinia sp. (Amoebozoa: Thecamoebida) and Rosculus sp. (SAR: Cercozoa) Isolated From King Penguin Guano Collected in the Subantarctic (South Georgia, Salisbury Plain) and their Coexistence in Culture - Tyml, Tomáš; Dyková, Iva (The Journal of eukaryotic microbiology, 2018)
Two amoeboid organisms of the genera Sappinia Dangeard, 1896 and Rosculus Hawes, 1963 were identified in a sample containing king penguin guano. This sample, collected in the Subantarctic, enlarges the list of fecal habitats known for the presence of coprophilic amoebae. The two organisms were co-isolated and subcultured for over 6 mo, with continuous efforts being invested to separate each one from the mixed culture. In the mixed culture, Rosculus cells were fast growing, tolerated changes in culturing conditions, formed cysts, and evidently were attracted by Sappinia trophozoites. The separation of the Rosculus strain was accomplished, whereas the Sappinia strain remained intermixed with inseparable Rosculus cells. Sappinia cell populations were sensitive to changes in culturing conditions; they improved with reduction of Rosculus cells in the mixed culture. Thick-walled cysts, reportedly formed by Sappinia species, were not seen. The ultrastructure of both organisms was congruent with the currently accepted generic characteristics; however, some details were remarkable at the species level. Combined with the results of phylogenetic analyses, our findings indicate that the ultrastructure of the glycocalyx and the presence/absence of the Golgi apparatus in differential diagnoses of Sappinia species require a critical re-evaluation.
Keywords: fylogeneze; Ecosystem; molecular phylogeny; Georgia; free-living amoebae; HGR clade; Spheniscidae; Coprophilic amoebae; ultrastructure; feces; Cercozoa; zvířata; Animals; Phylogeny; polar region; ekosystém; Amoebozoa; Feces